A STUDY OF FACTORS AFFECTING THE LEVEL OF HAPPINESS AMONGST PRACTITIONERS OF YOGA, AEROBICS AND WALKING DURING CORONA LOCKDOWN - Singh, Vikram; Yaduvanshi, Pragyendu; Singh, Karan (International Journal of Research -GRANTHAALAYAH, 2021)
Fitness and Yoga has been the focus of studies in recent decades for the not only the general well-being but also a therapeutic modality for mental stress, obesity, and other lifestyle disorders. Individual studies indicate positive effects of exercises like aerobics, walking and yoga under covid-19 lockdown conditions, suggesting that they can be used as non-pharmacological and as non-invasive interventions or as a supplement to drug therapy for the prevention and treatment of various mental and physical conditions. 120 moderately active healthy males (59) and females (61) volunteered to participate in the survey study with the aim to study the level of happiness and related variables age, body mass index, level of education and choice of physical activity of the participants. Oxford Happiness Questionnaire (OHQ) developed by psychologists Michael Argyle and Peter Hills at Oxford University was used to collect data. Results showed that there was no statistically significant difference in the choice of activity out of the three namely: aerobics, yoga and walking to stay fit and healthy. The level of happiness was found to be better for those who spent a greater number of years in school/college/university and another finding was that the level happiness was lower amongst the participants who were of more age as compared to the ones who were of lesser age. There was a significant difference in the level of happiness amongst the walkers, aerobic practitioners and yoga practitioners. It was not possible however to point out exactly the magnitude of difference between the three groups because the data was non-parametric. No gender differences were observed amongst males and females on level of happiness on activities chosen by the participants (aerobics, yoga and walking) to stay fit and healthy. Significant differences amongst the participants were observed amongst the underweight, normal weight and overweight participants